A Coherent Distributed File Cache with Directory Write-behind - Birrell, Andrew (ACM Transactions on Computer Systems, 1994)
Extensive caching is a key feature of the Echo distributed file system. Echo client machines maintain coherent caches of file and directory data and properties, with write-behind (delayed write-back) of all cached information. Echo specifies ordering constraints on this write-behind, enabling applications to store and maintain consistent data structures in the file system even when crashes or network faults prevent some writes from being completed. In this paper we describe the Echo cache’s coherence and ordering semantics, show how they can improve the performance and consistency of applications, and explain how they are implemented. We also discuss the general problem of reliably notifying applications and users when write-behind is 10SE we addressed this problem as part of the Echo design, but did not find a fully satisfactory solution.
A preliminary version appeared as SRC Research Report 103